An Overview of Recent Advances in Pursuit–Evasion Games with Unmanned Surface Vehicles - Xingru Qu; Linghui Zeng; Shihang Qu; Feifei Long; Rubo Zhang (Journal of Marine Science and Engineering)
With the rapid development of perception, decision-making, and control technologies, pursuit–evasion (PE) games with unmanned surface vehicles (USVs) have become an interesting research topic in military implementations and civilian areas. In this paper, we provide an overview of recent advances in the PE games with USVs. First, the motion model of USVs and successful criteria for PE games are presented. Next, some challenging issues in PE games with USVs are briefly discussed. Then, recent results on one-pursuer one-evader, multiple-pursuer one-evader, and multiple-pursuer multiple-evader with USVs are reviewed in detail. Finally, several theoretical and technical issues are suggested to direct future research, including target prediction, dynamic task allocation, brain-inspired decision-making, safe control, and PE experiments.